Self- but Not Other-Dimensions of Mentalizing Moderate the Impairment Associated With Social Anxiety in Adolescents From the General Population - Ballespí, Sergi; Vives, Jaume; Nonweiler, Jacqueline; Perez-Domingo, Ariadna; Barrantes-Vidal, Neus (Frontiers in Psychology, 2021)
Mentalizing, or social cognition, refers to the brain’s higher order capacity that allows humans to be aware of one’s own and others’ mental states (e.g., emotions, feelings, intentions). While cognition in social anxiety has been broadly analyzed, social cognition is less well-researched. Moreover, mentalizing or social cognition research is traditionally focused on the understanding of others’ mental states, rather than self-mentalizing. Finally, most studies analyze the role of social cognition in the development or maintenance of social anxiety, yet no study to date has analyzed whether social cognition moderates functional impairment associated with it. This study analyzes whether self- and other- mentalizing moderate the relationship between social anxiety and impairment in social and self-functioning. A sample of 262 adolescents from the non-clinical population was assessed on measures of social anxiety, self- and other- mentalization, indicators of social functioning (social competence and sociometric status), and indicators of self-functioning (depression and self-esteem). Multivariate linear regressions were conducted to test possible moderation effects of self-mentalizing and other-mentalizing on the relationships between social anxiety and social and self-functioning. Results revealed that other-mentalizing does not moderate social- nor self-functioning, while self-mentalizing moderates the impairment of all of them. While impairment in social functioning is buffered by one dimension of self-mentalizing (emotional clarity; b=.003 , p=.043 and b=.016 , p=.008 for social competence and sociometric status, respectively), impairment in self-functioning is strengthened by the other dimension (attention to emotions; b=-.007 , p=.008 and b=.009 , p=.047 for self-esteem and depression, respectively). Probing the moderation at the 16th, 50th, and 84th percentiles revealed that the negative imbalance between dimensions (i.e., high attention and low clarity) tended to exacerbate impairment most on all indicators, while the positive imbalance (i.e., low attention and high clarity) was usually the most buffering condition. This supports that ‘low-flying’ or implicit mentalizing provides more resilience than explicit mentalizing (i.e., high attention and high clarity). Findings suggest that the work on emotional self-awareness should be stressed in the intervention of the social anxiety spectrum conditions in order to improve prevention, functioning, and ultimately, treatments, of people impaired by symptoms of social anxiety.